Zeolite‐loaded alginate‐chitosan hydrogel beads as a topical hemostat. Issue 5 (26th August 2017) - Fathi, Parinaz; Sikorski, Michael; Christodoulides, Katerina; Langan, Kristen; Choi, Yoon Sun; Titcomb, Michael; Ghodasara, Anjali; Wonodi, Omasiri; Thaker, Hemi; Vural, Mert; Behrens, Adam; Kofinas, Peter
Abstract: Hemorrhage is the leading cause of preventable death after a traumatic injury, and the largest contributor to loss of productive years of life. Hemostatic agents accelerate hemostasis and help control hemorrhage by concentrating coagulation factors, acting as procoagulants and/or interacting with erythrocytes and platelets. Hydrogel composites offer a platform for targeting both mechanical and biological hemostatic mechanisms. The goal of this work was to develop hydrogel particles composed of chitosan, alginate, and zeolite, and to assess their potential to promote blood coagulation via multiple mechanisms: erythrocyte adhesion, factor concentration, and the ability to serve as a mechanical barrier to blood loss. Several particle compositions were synthesized and characterized. Hydrogel bead composition was optimized to achieve the highest swelling capacity, greatest erythrocyte adhesion, and minimal in vitro cytotoxicity. These results suggest a polymer hydrogel‐aluminosilicate composite material may serve as a platform for an effective hemostatic agent that incorporates multiple mechanisms of action. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1662–1671, 2018.